Penyediaan Biofilm Berbasis Pektin Kulit Buah Cempedak (Artocarpus champaden L.) Terisi Carboxymethyl Cellulose dengan Variasi Konsentrasi Gliserol Untuk Menurunkan Susut Bobot Buah Mangga - Batu Bara, Fachreza Amri; Pratama, Muhammad A.; Ginting, Muhammad Hendra S.; Harahap, Hamidah; Dalimunthe, Nisaul Fadilah; Al Fath, Muhammad Thoriq (Jurnal Teknik Kimia USU, 2025)
Cempedak peel contains 38.85% pectin compounds and has the potential to become biofilm raw material. The characteristics of pectin-based biofilm can be improved by the addition of a glycerol plasticizer. This study aims to determine the effect of variations in glycerol concentration (0%; 3%; 5%; 7% and 9%) on biofilm charactersitics and biofilm application on the shelf life of mango fruit. Pectin was extracted using 5% citric acid at 85°C or 90 minutes. Biofilms were applied on mango fruit for 8 days. Analysis of pectin compounds showed a yield 22.09%; ash content 7.40%; equivalent weight 588.235 mg; methoxyl content 6.20%; galacturonic acid content 36.12%. Analysis of physical properties and biofilm application on mango fruit showed a density value of 2.833 g/mL; water solubility 79.41%; mango weight loss of 33.47%; and a deacrease in vitamin C of 5%. SEM-EDX analysis showed the pectin particles were homogeneous fine grains and dominated by the element of oxygen (O) 88.84%. FTIR analysis of cempedak fruit peel pectin and biofilm showed functional groups of O-H; C-H (methyl); C=O; C-O; C-C.